Roads and traffic autumn 1994 - Swedish Road Administration (Swedish Transport Administration, 1997)
This is the third survey in a series of surveys measuring and following up the general public´s experiences and usage of Swedish roads, and looking into how the products and services of the National Road Administration are received by the users. Questions on the respondent´s experiences as a driver and usage of vehicles includes holding of driving license, number of miles driven by car during the last 12 months, size of car driven, car equipment, how often the respondent had driven different vehicles during the last 12 months, how dependent the respondent is on a car, if the car usage will increase or decrease within the next five years, and reasons for changes in car usage. One section of the questionnaire is dedicated to roads; how often the respondent uses different kinds of roads, and how they are graded by the respondents, and in which fields the National Road Administration has to increase or decrease their efforts. The respondents have to give their opinion on the importance of dealing with a number of public issues, such as environmental pollution, care of elderly and children, the budget deficit, unemployment, health care etc. For a number of risks in traffic the respondents have to state how dangerous they count them to be. They also have to give their opinion on different threats against the environment and to tell what they are doing themselves to save the environment, and their opinion on how to drive adjusted to the environment. A number of questions deals with the traffic environment, how often the respondent is exposed to different environmental problems and how troublesome he/she counts them to be. Other questions deal with the knowledge and usage of different channels for information on road and weather conditions. The respondents also have to give their opinion on the National Road Administration in general, and how it is dealing with road safety issues and environmental issues. Background information includes gender, age, place of living, size of household, and number of children under the age of 16.

This is the third survey in a series of surveys measuring and following up the general public´s experiences and usage of Swedish roads, and looking into how the products and services of the National Road Administration are received by the users. Questions on the respondent´s experiences as a driver and usage of vehicles includes holding of driving license, number of miles driven by car during the last 12 months, size of car driven, car equipment, how often the respondent had driven different vehicles during the last 12 months, how dependent the respondent is on a car, if the car usage will increase or decrease within the next five years, and reasons for changes in car usage. One section of the questionnaire is dedicated to roads; how often the respondent uses different kinds of roads, and how they are graded by the respondents, and in which fields the National Road Administration has to increase or decrease their efforts. The respondents have to give their opinion on the importance of dealing with a number of public issues, such as environmental pollution, care of elderly and children, the budget deficit, unemployment, health care etc. For a number of risks in traffic the respondents have to state how dangerous they count them to be. They also have to give their opinion on different threats against the environment and to tell what they are doing themselves to save the environment, and their opinion on how to drive adjusted to the environment. A number of questions deals with the traffic environment, how often the respondent is exposed to different environmental problems and how troublesome he/she counts them to be. Other questions deal with the knowledge and usage of different channels for information on road and weather conditions. The respondents also have to give their opinion on the National Road Administration in general, and how it is dealing with road safety issues and environmental issues. Background information includes gender, age, place of living, size of household, and number of children under the age of 16.
Vägar och trafik hösten 1994
Keywords: Wounds and injuries; Sår och skador; Information society; Informationssamhället; Environment and conservation; Miljö och naturvård; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap